Repeated hexanucleotide C-C-C-C-A-A is present near free ends of macronuclear DNA of Tetrahymena. - Yao, M C (1981)
The tandemly repeated hexanucleotide C-C-C-C-A-A has previously been found near the termini of extrachromosomal gene coding for ribosomal RNA as well as in many other locations of the genome of Tetrahymena. Moreover, the organization of these clusters of repeats in the somatic macronucleus is different from that in the germinal micronucleus. In this study we used the exonuclease Bal 31 to show that the repeats are located near free ends of DNA in the macronucleus. When whole cell DNA or macronuclear DNA was digested with Bal 31 to remove approximately 600 base pairs from free ends, 80% of the C4A2 repeats were removed, as judged by hybridization. Because no particular cluster was resistant to exonuclease digestion, we believe that essentially all the C4A2 repeats are located near free ends of DNA. The C4A2 repeats in the micronucleus, on the other hand, were not digested by Bal 31.